Goat locker strikes! - Shandrow, Steve (Bookstand Publishing, 2012)
"Oceans across the globe are erupting in piracy, drug smuggling, and all out anarchy. Retired Navy Master Chief Bob Kensey knew all about the unrest, but nothing of the dark storm clouds brewing two oceans and thousands of miles away. His thoughts were on the two Chinook salmon caught earlier, now simmering in the smoker, and beating Gunny, the "Safe Haven" bar's proprietor out of another cold San Magoo beer. Life changes for the chief when a sailing yacht is hijacked off the coast of Somalia and an unannouced visit by a shipmate from the past set wheels in motion that engulfs Chief Kensey, and a hastily recruited crew of irascible old goats on a mission destined to fail. With years of experience to call upon, and a well-placed government official to help, they undertake a mission that can only be described as the very definition of "off-the-grid".-- back cover